Use Technology In Developing English Speaking Club at STMIK Royal - Cecep Maulana (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2018)
The study is aimed to find out whether there is a significant difference in the speaking ability between the First Semester of STMIK Royal in Kisaran who were taught by Technology video and those who were not, in the academic year of 2016/2017. This research was classified as a quasi-experimental study. It involved 68 students of two groups for mojoring information System, semester 1 for class G as the experimental group and Class H as the control group. The experimental group was taught using video, whereas the control group was taught using the module-based technique for English Speaking Club (ESC) at STMIK Royal in Kisaran. The results of the research show that there is a significant difference in the English speaking Club (ESC) between the students who were taught by video and those who were taught by using the textbook-based technique. The significance value calculated 0.000 is smaller than 0.05 (P-value = 0.000 < 0.05). Therefore, the hypothesis of this study is accepted. It means that the video technique significantly improves the students’ speaking ability in the English teaching at Stmik Royal in Kisaran for ESC. Keywords: english language teaching, technology video, english speaking club